Effect of single dose N-acetylcysteine administration on resting state functional connectivity in schizophrenia - McQueen, Grant (Psychopharmacology (Berl), 2019)
RATIONALE: There is interest in employing N-acetylcysteine (NAC) in the treatment of schizophrenia, but investigations of the functional signatures of its pharmacological action are scarce. OBJECTIVES: The aim of this study was to identify the changes in resting-state functional connectivity (rs-FC) that occur following administration of a single dose of NAC in patients with schizophrenia. A secondary aim was to examine whether differences in rs-FC between conditions were mediated by glutamate metabolites in the anterior cingulate cortex (ACC). METHODS: In a double-blind, placebo-controlled crossover design, 20 patients with schizophrenia had two MRI scans administered 7 days apart, following oral administration of either 2400 mg NAC or placebo. Resting state functional fMRI (rsfMRI) assessed the effect of NAC on rs-FC within the default mode network (DMN) and the salience network (SN). Proton magnetic resonance spectroscopy was used to measure Glx/Cr (glutamate plus glutamine, in ratio to creatine) levels in the ACC during the same scanning sessions. RESULTS: Compared to the placebo condition, the NAC condition was associated with reduced within the DMN and SN, specifically between the medial pre-frontal cortex to mid frontal gyrus, and ACC to frontal pole (all p < 0.04). There were no significant correlations between ACC Glx/Cr and rs-FC in either condition (p > 0.6). CONCLUSIONS: These findings provide preliminary evidence that NAC can reduce medial frontal rs-FC in schizophrenia. Future studies assessing the effects of NAC on rs-FC in early psychosis and on repeated administration in relation to efficacy would be of interest. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00213-019-05382-1) contains supplementary material, which is available to authorized users.